Pemberdayaan Petani dan Peternak Desa Warnasari untuk Menciptakan Petani dan Peternak Yang Mandiri dan Berdaya Saing - Ferryal Abadi; Triyono Arief Wahyudi; Menik Indrati; Muniroh Muniroh; Ria Estiana (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This Community Service activity aims to enhance the capacity of farmers and livestock breeders through an empowerment program focused on strengthening knowledge, skills, and business independence. The implementation method uses a participatory approach. Activities are carried out by involving farmer groups, livestock groups, village government, and the implementation team as partners in every stage of the program. The results of the activities show an increase in participants' knowledge and skills in the application of cultivation techniques, business management, product processing, as well as the utilization of digital technology to support product marketing. In addition, participants have begun to implement simple business record-keeping, strengthen cooperation between groups, and increase awareness of the importance of innovation in developing agricultural and livestock businesses. The participatory approach implemented has been able to increase community involvement, ensuring that the program aligns with local needs and provides more sustainable benefits.